The biology of blood-sucking in insects - Lehane, M. J (Cambridge University Press, 2005)
They love you very much, and they are very ugly. In this compendium of facts about insects that bring a broad range of misery to humans and animals, Lehane (Liverpool School for Tropical Medicine) takes a topical rather than taxonomic approach as he describes their importance in terms of health, their feeding preferences, the location of the host, ingestion of the blood meal, management of the blood meal, host-insect interaction, transmission of parasites, and blood-sucking insect groups and provides illustrations.